IDT164 : Experimental construction / Faculty of Art and Design - UiTM, Faculty of Art and Design (Universiti Teknologi MARA (UiTM), 2023)
This course is an experimental approach merging technical and creativity, to enable students in understanding the problem and defining the solution in creative ways. This course explained the significant of creative technical thinking which is applicable to solve the task given. It is also used to develop the ways of thinking to get the solution of any consequences in design process. These aspects concentrate in: • Basic of experimental study • Experimental of material • Experimental of weight • Experimental of height • Experimental of construction • Experimental of sound